The effect of demographic factors, occupational stress and job satisfaction towards dysfunctional audit behavior among auditors in Malaysia / Maizatul Akmam Mansor, Norazian Hussin and Rina Fadhilah Ismail - Mansor, Maizatul Akmam; Hussin, Norazian; Ismail, Rina Fadhilah (Faculty of Accountancy, 2019)
The impact of dysfunctional audit behaviour has asserted the regulators’ concern as it will reduce audit quality and the ability of auditor in detecting fraud. It is important for an audit firm to detect the factors that can influence dysfunctional behaviour. The decreasing in dysfunctional audit behaviour among auditors will directly and indirectly affect the audit firm since it can offer numerous benefits to the audit client and external parties, investor, financial institution and future investor as the auditor will produce a higher quality of financial statement. Hence, this study aims to examines the factors of dysfunctional behavior among auditors in Malaysia. Factor analysis was employed to analyse three factors (1) demographic factors (type of firm and period of audit experience), (2) Occupational stress (time budget pressure and complexity of audit task) and (3) Job Satisfaction that affect dysfunctional audit behavior which is reduced audit quality and underreporting time. A survey in a form of questionnaire was distributed to Big 4 and non-Big 4 in Kuala Lumpur and Selangor resulted in a total of 223 respondents. The findings revealed that all the tested variables have a significant influence towards reduced audit quality whereas underreporting time show a non-significant relationship with demographic factors. The findings are anticipated to provide beneficial insights not only to audit practitioners but to many other regulators, professional bodies, policy makers, practitioners and academics that are relevant to their future decisions. This study is also subject to limitations that serve as consideration for future research.